Exploring associations between the use of alcohol and marijuana with e-cigarette use in a U.S.A. nationally representative sample of young adults - Bluestein, Meagan; Kelder, Steven; Perry, Cheryl L.; Pérez, Adriana (International Journal of Health Sciences, 2018)
Objectives: Previous research has shown that e-cigarette use is rising among young adults, but it is unknown whether the dual use of alcohol and marijuana is associated with e-cigarette use in a U.S.A. nationally representative sample. Methodology: Secondary analysis of the Population Assessment of Tobacco and Health 2013–2014 nationally representative sample of young adults (aged 18–24) was conducted to examine the relationships between dual ever and dual current use of alcohol and marijuana with e-cigarette use. Multiple logistic regression models were used to explore the associations between dual ever and dual current use alcohol and marijuana with two outcomes: Past 30 days and former experimental e-cigarette use. Covariates included sex, race/ethnicity, education level, household income, and the total number of tobacco products ever used. Results: Dual ever use of alcohol and marijuana was significantly associated with past 30 days use (adjusted odds ratio [AOR] = 2.20; 95% confidence interval [CI] = 1.67–2.91) and former experimental e-cigarette use (AOR = 2.82; 95% CI = 2.23–3.57). Exclusive ever marijuana use was also significantly associated with each outcome, while exclusive ever alcohol use was associated with former experimental e-cigarette use. Exclusive current marijuana use, exclusive current alcohol use, and dual current use of both substances were significantly associated with past 30-day e-cigarette use, but not former experimental e-cigarette use. Conclusions: These findings indicate that young adult dual users of marijuana and alcohol have increased odds of e-cigarette use. In addition, exclusive current and ever marijuana users had the highest odds e-cigarette use, higher than young adult dual users of alcohol and marijuana, indicating that marijuana users may be an important group to target with intervention programs.